PENGARUH SERTIFIKAT HALAL, KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN MIE GACOAN YOGYAKARTA - Nurida Afiani Nugroho (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2025)
This study aims to analyze the effect of halal certificates, service quality, and price perceptions on consumer satisfaction of Gacoan Noodles in Yogyakarta. The research method used is quantitative with an associative approach. The sample used was 100 respondents with purposive sampling technique. Data analysis was performed with multiple linear regression using Eviews 12. The results showed that halal certificates, service quality, and price perceptions had a positive and significant effect on customer satisfaction. This proves that these three variables have an important role in creating customer satisfaction, especially in the context of the fast food industry which is growing rapidly. This research also reinforces the relevance of applying sharia principles in the culinary business in Indonesia.